2012
DOI: 10.4103/0301-4738.103799
|View full text |Cite
|
Sign up to set email alerts
|

Unusual optical coherence tomography and fundus autofluorescence findings of eclipse retinopathy

Abstract: A 63-year-old female patient complained of dimness in the central field of vision in the left eye after viewing an annular partial eclipse without adequate eye protection on 22 July 2009. Fundoscopy showed a wrinkled macular surface. Fundus autofluorescence study revealed well-demarcated hyperautofluorescence at the fovea. Optical coherence tomography demonstrated tiny intraretinal cysts. Fluorescein angiography and indocyanine green angiography were unremarkable. Epimacular membrane developed in the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This situation is called blue light hazard. Acute damage to the retina by accidentally gazing at sun light, arc welding light, laser light from medical and industrial equipment, and light emission diodes used in toys has been reported [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, the harmfulness of chronic exposure to blue light of certain wavelengths is still controversial [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…This situation is called blue light hazard. Acute damage to the retina by accidentally gazing at sun light, arc welding light, laser light from medical and industrial equipment, and light emission diodes used in toys has been reported [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, the harmfulness of chronic exposure to blue light of certain wavelengths is still controversial [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The lesion fades over several weeks without significant damage (Fig. 4b) or causes abnormalities including foveal pigment mottling, lamellar holes, and/or epiretinal membranes [6,[136][137][138]. Visual acuity usually decreases to 20/ 40-20/200 immediately after an injury but returns to the 20/20-20/40 level over the following 6 months [136,139].…”
Section: Clinical Featuresmentioning
confidence: 99%